Effects of ethical climate on organizational commitment, professional commitment and job satisfaction of auditors in Malaysia - Ismail, Suhaiza (Universitas Gadjah Mada, 2015)

(untitled)
The objective of this paper is to investigate the effect of the ethical climate on the organizational commitment, professional commitment and job satisfaction of Malaysian auditors. Using a survey questionnaire comprising instruments about the ethical climate, organizational commitment, professional commitment and job satisfaction, 263 usable responses were received. To achieve the objectives, mean scores, standard deviations, correlations and multiple regressions were performed. The study revealed that a significant positive influence of a caring ethical climate on professional and organizational commitment as well as job satisfaction existed. There was also a positive significant association between the law and code ethical climate and professional commitment. On the other hand, the study discovered that the instrumental ethical climate type had a significant negative relationship with organizational commitment and job satisfaction. A significant negative relationship was also revealed between the independent ethical climate type and organizational and professional commitment. A significant negative relationship between the rules ethical climate and job satisfaction was also discovered.